Analisis Tarif Angkutan Paratransit Berdasarkan Ability To Pay dan Willingness To Pay Rute Banda Aceh - Medan - Mutiawati, Cut; Sastra, Muhammad Defri; Suryani, Fitrika Mita (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2023)
Paratransit Transportation is a system of using public transportation whose services are provided by the operator and can be used by everyone. Hiace public transportation is one of the public transportations used by the community as a mode of transportation that uses the Paratransit system. The determination of the Hiace transportation fare is something that has a direct effect on the usability of the community. The problem discussed in this study is to determine the ideal Hiace transportation fare based on Ability To Pay and Willingness To Pay. The purpose of this study was to determine the characteristics of Hiace public transport users on the Banda Aceh – Medan route and evaluate Hiace fares based on Ability To Pay (ATP) and Willingness To Pay (WTP). This research consists of collecting data, namely primary data and secondary data. Primary data was obtained by distributing questionnaires to Hiace transportation users on the Banda Aceh – Medan route. The method of data collection was carried out by distributing questionnaires using a google form link and the Stated Preference technique by directly providing alternative answers to each question. While secondary data was obtained from the relevant agencies as a basis for determining the population of Hiace transport users. The basic fare for Hiace transportation for the Banda Aceh – Medan route is currently IDR 240,000. The results obtained from this study are the ideal Hiace transportation fare in terms of passengers as users of Hiace transportation services based on Ability To Pay (ATP) which is Rp. 213,000.00 and Willingness To Pay (WTP) which is Rp. 238,000.00. The value of the ATP rate is below the WTP rate, this illustrates that Hiace users are a group of captive riders who have low income but want to pay above their ability to pay. User satisfaction on this transportation is good, with an average satisfaction score of 3.9 out of 5.